Improved model-free sliding mode control of permanent magnet synchronous motor drive system based on quick reaching law - HUANG Yishan; TANG Runzhong; KUANG Mingqiu; LIU Jianhua; ZHAO Kaihui; CHENG Xiang (机车电传动)
To solve the problem that the overall control performance of permanent magnet synchronous motor (PMSM) drive system does not achieve the expected performance index when using conventional model-free sliding mode control (CMFSMC) algorithm, an improved MFSMC based on the quick reaching law was proposed. Firstly, according to the mathematical model of PMSM with parameter perturbation, an ultra-local model of the speed loop in the PMSM was established. Secondly, a new MFSMC in speed loop was designed by using an improved quick reaching law. Meanwhile, to improve the control accuracy of motor speed, the extended sliding mode observer (ESMO) was utilized for the real-time observation of the unknown part of the ultra-local model. Finally, compared with PI control and CMFSMC algorithm, the simulation and experimental results verified that the proposed method could reduce the dependence on the PMSM model, improve the transient steady-state control performance of PMSM, and guarantee anti-interference ability and strong robustness of the system.